Natural disasters and acceptance of intimate partner violence: The global evidence - Astghik Mavisakalyan; Vladimir Otrachshenko; Olga Popova (Global Labor Organization (GLO), 2024)
This paper examines the dynamic impact of natural disasters on the individual acceptance of a physical form of intimate partner violence (IPV). Based on a global sample of individual survey data and historical geo-referenced records of natural disasters at a subnational level, we show that natural disasters have long-lasting effects on IPV acceptance, increasing it in the short- (0-4 years) and medium- (10- 14 years) run. Furthermore, heterogeneity analyses reveal that lower educated people are affected more relative to higher educated people, men are affected more than women, as are older cohorts relative to younger cohorts, while there are no differences between the effects of disasters on IPV attitudes of people with high and low income. Drawing on theories of IPV, we also uncover that likely mechanisms that may link disasters to the increased acceptance of IPV are psychological distress and economic insecurity fears.
Keywords: J12; I31; P37; Q54; 330; natural disasters; intimate partner violence; domestic abuse